Implementation of the Project Strengthening Profile of Pancasila Students with Ecotourism Education in Ciletuh-Palabuhanratu UNESCO Global Geopark Area: A Case Study in Secondary School - Rahma Dewi Hartati; Achmad Anwar Abidin; Imam Yusuf Badrut Tamam; Junaenti Junaenti (Journal of Innovation in Educational and Cultural Research, 2025)
This research is motivated by the Emancipated Curriculum, which provides flexibility for teachers to create learning that suits the needs and environment of students, including through the Pancasila Student Profile Strengthening Project (P5). P5 is an educational initiative that aims to instill Pancasila values in students, covering aspects such as mutual cooperation, independence, critical reasoning, creativity, and global diversity. This study explores the implementation of P5 through ecotourism education in the Ciletuh-Palabuhanratu UNESCO Global Geopark area and its contribution to achieving the Sustainable Development Goals (SDGs). The research method used is qualitative research with a case study approach. The study results show that ecotourism activities, such as tree planting, geological exploration, environmental awareness campaigns, and local cultural visits, have succeeded in increasing students' environmental awareness, social responsibility, and understanding of local culture. In addition, this activity supports the achievement of the SDGs, especially in quality education, decent work, and action on climate change. Thus, this activity succeeded in instilling Pancasila values such as cooperation, independence, critical reasoning, creativity, and global diversity in students. This research contributes to the development of science on applying ecotourism education, which can be a model for other schools to prepare students to face global challenges and preserve the surrounding environment.